Prebiotic capacity of novel bioengineered wheat arabinoxylans in a batch culture model of the human gut microbiota - Njoku, Emmanuel N.; Mottawea, Walid; Hassan, Hebatoallah; Hammami, Riadh (Frontiers in Microbiomes, 2023)
Arabinoxylan (AX) is an essential component of dietary fiber with potential prebiotic properties. However, owing to its complex structure, fermentation of AX by gut microbes is structure-dependent. In this study, we evaluated the effect of bioengineered wheat arabinoxylan on the metabolism and composition of the gut microbiota using an in vitro fermentation model. We compared the effect of bioengineered arabinoxylan with that of untreated arabinoxylan and a control. Structurally modified AX did not significantly alter gut microbiome composition within 48 h of treatment. However, it enhanced the abundance of health-promoting bacterial taxa, such as Bacteroides, Bifidobacterium, Anaerofustis, and Eubacterium. Furthermore, the bioengineered AX significantly increased the level of acetate produced over 24 h. The amount of microbiota-generated butyrate was significantly increased 24 h after adding α-L-arabinofuranosidase-treated AX. AX treated with the α-L-arabinofuranosidase B25 enzyme induced higher production of total short-chain fatty acids by the microbiota from four donors. The results of this study provide evidence that enzymatic-structural modification of AX has the potential to modulate gut microbiome composition and metabolic activities.